2023
DOI: 10.1037/aap0000316
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relations between family cultural socialization and bicultural identity integration in burmese college students of refugee background.

Abstract: Burmese refugees represent one of the largest resettled populations in the United States in recent decades, but their postresettlement adjustment has scarcely been studied. Although resettlement presents a variety of opportunities and challenges for many refugee families, such as learning to navigate between heritage and mainstream cultures, the bicultural experiences of youth of refugee background are marginally understood. Considering that making sense of one’s relationship to culture and race/ethnicity is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…(2018) found the relation to ethnic identity affirmation to be mediated by conflict but only at high levels of parent‐child acculturation differences. Shein and Zhou (2023) found that among Burmese refugee youth, cultural socialization was positively correlated with bicultural blendedness but not bicultural harmony. Finally, cultural socialization was positively related to racial identity, including centrality and private regard (French et al., 2013), and American identity but only for females (Gartner et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2018) found the relation to ethnic identity affirmation to be mediated by conflict but only at high levels of parent‐child acculturation differences. Shein and Zhou (2023) found that among Burmese refugee youth, cultural socialization was positively correlated with bicultural blendedness but not bicultural harmony. Finally, cultural socialization was positively related to racial identity, including centrality and private regard (French et al., 2013), and American identity but only for females (Gartner et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Future research on AAPIs can also draw from the lessons on Latinx families' immigration socialization (Ayón, 2018) and examine how and to what extent parents convey messages about nativity, immigration, citizenship, and detention/deportation. It can also draw on lessons from research on Asian American parents' efforts to encourage acculturation and influence children's identities (Kim & Hou, 2016; Shein & Zhou, 2023). In addition to measuring a more complete set of ERS strategies, scholars should consider analyzing profiles of ERS strategies (e.g., Atkin & Ahn, 2022; Atkin & Yoo, 2021) which would enable assessment of messaging coherence and its relation to outcomes (Atkin & Yoo, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Knight et al (2011) explore the familial socialization of culturally related values in Mexican American families, highlighting the strategies parents use to instill cultural values in their children (Knight et al, 2011). Similarly, Shein and Zhou (2023) examine the relations between family cultural socialization and bicultural identity integration in Burmese college students of refugee background, shedding light on the long-term impacts of these processes (Shein & Zhou, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, high social competence can serve as a protective factor, helping individuals navigate the challenges of marginalization more effectively (Shein & Zhou, 2023). Understanding how these variables interact is crucial for developing interventions that support marginalized individuals and enhance family functioning.…”
Section: Introductionmentioning
confidence: 99%